2017
DOI: 10.5348/ijbti-2017-29-oa-2
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of transfusion transmitted infections: A focus on hepatitis B virus among blood donors at Hawassa blood bank center, Southern Ethiopia

Abstract: Aims: Millions of lives are saved each year through blood transfusion but a safe blood supply is a critical component of health care to prevent the spread of blood-borne infectious diseases. Therefore, it is essential to assess the prevalence and identify the most common culprit and risk in transfusion services. Methods A cross-sectional study was conducted from April 2015 to May 2015 at the Hawassa blood bank center. Blood donors who donated blood for transfusion purposes were considered for the study. Whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
26
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 24 publications
6
26
5
Order By: Relevance
“…The 0.25% prevalence rate of HIV among blood donors in North Shewa zone was lower than the previous reports from Gondar (2.24%), Jimma (2.1%), Hawassa (1.6%) and Wolayita Sodo (6.4%), Ethiopia [ 9 , 15 , 16 , 25 ]. This could be due to differences in sociodemographic risks factors, HIV prevalence in the general population, health education programs, and donor selection schemes across the study areas.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…The 0.25% prevalence rate of HIV among blood donors in North Shewa zone was lower than the previous reports from Gondar (2.24%), Jimma (2.1%), Hawassa (1.6%) and Wolayita Sodo (6.4%), Ethiopia [ 9 , 15 , 16 , 25 ]. This could be due to differences in sociodemographic risks factors, HIV prevalence in the general population, health education programs, and donor selection schemes across the study areas.…”
Section: Discussioncontrasting
confidence: 62%
“…In this study, we found that 2.4% of the donated blood was tested seropositive for at least one of the screened TTIs. This was relatively a low prevalence when compared to the rates reported from other parts of Ethiopia, which ranged from 6.6% to 29.5% [ 7 , 9 , 15 , 16 ]. Several explanations can be put forward for the lower prevalence of TTIs in this study.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations